2001
DOI: 10.1029/2001gl013722
|View full text |Cite
|
Sign up to set email alerts
|

Formation of molecular chlorine in dark condition: Heterogeneous reaction of ozone with sea salt in the presence of ferric ion

Abstract: Abstract. Uptake coefficients of 03 on NaC1 and synthetic sea salt (SSS) were found to be enhanced from < 10 -5 to • 3.5 x 10 -2 in the presence of water-soluble Fe 3+ in the Fe/Na weight ratio larger than 0.1%. C12 release was observed without radiation in the reaction of 03 and a FeC13/NaC1 mixture with surface adsorbed water at the yields of 0.48 and 0.28 for Fe/Na ratio of 1.0 and 0.5 weight %, respectively. Only Br2 release was observed for a FeC13/SSS sample. These results imply that when bromide is defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 28 publications
2
32
2
Order By: Relevance
“…This is produced at night, as well as during the day, from heterogeneous reactions of ozone with wet sea-salt and is enhanced by the presence of ferric ions (10). Employing a high-pressure chemical ionization mass spectrometry technique, Spicer et al (11) measured Cl 2 levels ranging from <15 to 150 pptv.…”
Section: Introductionmentioning
confidence: 99%
“…This is produced at night, as well as during the day, from heterogeneous reactions of ozone with wet sea-salt and is enhanced by the presence of ferric ions (10). Employing a high-pressure chemical ionization mass spectrometry technique, Spicer et al (11) measured Cl 2 levels ranging from <15 to 150 pptv.…”
Section: Introductionmentioning
confidence: 99%
“…Additional to iron photolysis, in a different and daytimeindependent chemical reaction, iron catalyzes the formation of q Cl or Cl 2 from chloride by tropospheric ozone (Sadanaga et al, 2001). Triggering the CH 4 decomposition, both kinds of iron and chlorine have a cooperative cooling effect on the troposphere: less GHG CH 4 in the atmosphere reduces the greenhouse (GH) effect and allows more outgoing infrared (IR) heat to the outer space (Ming et al, 2014).…”
Section: Oxidation Of Methane and Other Ghgsmentioning
confidence: 99%
“…[13] Concerning O 3 , Sadanaga et al [27] observed an enhancement of the O 3 uptake rate and Cl 2 release in the presence of water-soluble Fe 3þ and O 3 in the dark. When SO 2 is involved, the absorbed amount is highly pH-dependent.…”
Section: Introductionmentioning
confidence: 99%